2019
DOI: 10.1002/smll.201900288
|View full text |Cite
|
Sign up to set email alerts
|

High‐Indexed PtNi Alloy Skin Spiraled on Pd Nanowires for Highly Efficient Oxygen Reduction Reaction Catalysis

Abstract: The catalytic performance of Pt‐based catalysts for oxygen reduction reactions (ORR) can generally be enhanced by constructing high‐index exposed facets (HIFs). However, the synthesis of Pt alloyed high‐index skins on 1D non‐Pt surfaces to further improve Pt utilization and stability remains a fundamental challenge for practical nanocrystals. In this work, Pd nanowires (NWs) are selected as a rational medium to facilitate the epitaxial growth of Pt and Ni. Based on the different nucleation and growth habits of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 44 publications
0
34
0
2
Order By: Relevance
“…[21][22][23] Consequently, the rationale design of ligand coating of the electrocatalysts can potentially tune the activity and selectivity of metal nanoparticles in a wide range of catalytic reactions. [24][25][26][27] Organic linkers have recently emerged as promising strategy to increase the catalytic performances of nano-sized structures. Guo et al stated that the electron-donating properties of phosphine ligands (PPh3) magnify the surface electronic density of PdNPs improving the chemoselective catalytic hydrogenation of acetophenone.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Consequently, the rationale design of ligand coating of the electrocatalysts can potentially tune the activity and selectivity of metal nanoparticles in a wide range of catalytic reactions. [24][25][26][27] Organic linkers have recently emerged as promising strategy to increase the catalytic performances of nano-sized structures. Guo et al stated that the electron-donating properties of phosphine ligands (PPh3) magnify the surface electronic density of PdNPs improving the chemoselective catalytic hydrogenation of acetophenone.…”
Section: Introductionmentioning
confidence: 99%
“…The specific combinations of Pd@PtNi and Pd@FePt, in which Pd serves as the main component for core, have been reported by several groups. [96,[167][168][169][170][171][172] These studies reported that FePt and PtNi shells deposited on a Pd core had high catalytic activity and stability. However, the discussions regarding the role of Pd in the improved catalyst stability were not sufficiently clear.…”
Section: Ternary Core-shell Nanostructuresmentioning
confidence: 99%
“…这是因为Pt和Ni之间的协同作用 能 够 更 好 地 调 控 Pt的 电 子 结 构 [50] , 减 弱 Pt对 CO的吸附能力 [51] , 从而增强催化剂的抗CO中毒 能力. 的表面能 [32] , 更能减弱催化过程中溶解和奥斯特 瓦尔德(Ostwald)熟化对催化剂的影响 [21,22] , 有助 于保持良好的稳定性; 同时该链状结构固有的各向 异性和高的导电率, 将会更加有利于电子的转移和 传递 [29,52] ; b) 组成Pt-Ni CNPs的零维纳米颗粒具 有较小的尺寸, 能够增大催化剂的电化学比表面 积, 向外界提供更多的活性位点, 提高催化活性.…”
Section: Pt-niunclassified
“…近期的研究表 明, 以纳米棒 [23,24] 、纳米线 [25,26] 或纳米管 [27] 等形 式存在的一维Pt基金属纳米材料, 由于在酸性电 催化条件下较难发生溶解和奥斯瓦德熟化等现象, 在催化MOR时能表现出优异的催化稳定性 [26,28] . Tian等 [29] Tian等 [29] 的研究内容不同的是, 本工作是在反应 釜中直接合成具有富Pt表面的Pt-Ni CNPs, 并 且在反应中添加了葡萄糖作为还原剂, 适量的葡萄 糖和表面活性剂共同控制一维纳米晶体的成核和 生长动力学 [30] , 其中葡萄糖对纳米颗粒自组装成 一维纳米结构并保持稳定起关键作用 [31,32] . 此外, 合金化导致了Pt的晶格间距减小 [33,34] .…”
unclassified